2007
DOI: 10.1111/j.1528-1167.2007.01385.x
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate and dopamine receptors contribute to the lateral spread of epileptiform discharges in rat neocortical slices

Abstract: SUMMARYPurpose: The effects of AMPA-type glutamate receptor as well as dopamine D1 and D2 receptors on the lateral propagation of epileptiform field potentials (EFP) were studied across adjacent areas of rat neocortical tissues. Methods: Epileptiform burst discharges were induced by superfusion of Mg 2+ -free artificial cerebrospinal fluid. Simultaneous field potential recordings of EFP were obtained from four microelectrodes placed 2-3 mm apart across coronal slices in the third layer of the neocortex. The ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…EC was the bottommost of the slices in the chamber that superfused by ACSF. Drugs were applied in the same direction of the ACSF flow directly over EC to prevent drug diffusion to the other parts of the slice (Goda et al, ; Gorji et al, ). (iv) Forty‐five minutes after the first KCl injection, the second KCl application was performed (CSD 2).…”
Section: Methodsmentioning
confidence: 99%
“…EC was the bottommost of the slices in the chamber that superfused by ACSF. Drugs were applied in the same direction of the ACSF flow directly over EC to prevent drug diffusion to the other parts of the slice (Goda et al, ; Gorji et al, ). (iv) Forty‐five minutes after the first KCl injection, the second KCl application was performed (CSD 2).…”
Section: Methodsmentioning
confidence: 99%
“…The propagation of epileptiform discharges can be understood as a pulse of synchronous activity transmitted from one neuronal population to the next, involving a rapid process during which neighboring neurons are recruited to generate discharges throughout the spatial extent of the network [7] . Previous studies have revealed that an improved understanding of the propagation patterns of epileptiform discharges, such as pathways and speed, could provide valuable insights into understanding the mechanisms of epileptogenesis and lead to better treatment of patients with epilepsy [8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%